The Importance Of Input And Interaction In Second Language Acquisition - Maharsi, Ista (Journal of English and Education (JEE), 2011)
The role of input and interaction in second language acquisition has become an unavoidably essential issue to discuss. Abundant research has examined what, how, when, and why input can keep up language acquisition. Many theories are proposed and to some extent implemented and proved to be effective. However, controversies around the role of input are also inevitable. This paper will propose the importance of input and interaction in second language acquisition as were put forward and necessitated by many researchers, how particular input might result in various intakes and how interaction could facilitate output.